PENGARUH AKTIVITAS FISIK MAHASISWA TERHADAP DENYUT NADI DAN TEKANAN DARAH PADA MASA PANDEMI COVID-19 DI FAKULTAS KEDOKTERAN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - LIRI ANDIYANI; GUSBAKTI RUSIP (JURNAL ILMIAH MAKSITEK, 2022)
Physical exercise is an activity carried out to improve and maintain body fitness, and it is recommended for each individual to avoid various diseases. The effect of physical exercise can be in the form of a positive effect that is, it can inhibitor damage. Regular physical exercise with light to moderate intensity can increase endurance and body fitness. To determine the effect of student activity on changes in pulse rate and blood pressure during the COVID-19 pandemic at the Faculty of Medicine, Muhammadiyah University of North Sumatra. The type of research used is categorical analytic method with cross-sectional research design with 78 respondents. Most of the respondents were female, namely 51 (65,4%) and male as many as 27 people (34,6%). The most blood pressure category was found in the normal group, namely 57 people (73,1%) while the normal pulse category was 63 people (80,8%).There was an effect of student activity on blood pressure during the COVID-19 pandemic at the Faculty of Medicine, Muhammadiyah University of North Sumatra, showing p values of 0.003 and 0.004 (p<0,05).